Use of remote sensing to determine the relationship of early vigour to grain yield in canola (Brassica napus L.) germplasm - Cowley, R.; Luckett, D.; Moroni, J.; Diffey, Simon (CSIRO, 2014)
Early crop vigour in canola, as in other crops, is likely to result in greater competition with weeds, more rapid canopy closure, improved nutrient acquisition, improved water-use efficiency, and, potentially, greater final grain yield. Laborious measurements of crop biomass over time can be replaced with newer remote-sensing technology to aid data acquisition. Normalised difference vegetation index (NDVI) is a surrogate for biomass accumulation that can be recorded rapidly and repeatedly with inexpensive equipment. In seven small-plot field experiments conducted over a 4-year period with diverse canola germplasm (n = 105), we have shown that NDVI measures are well correlated with final grain yield. We found NDVI values were most correlated with yield (r >0.7) if readings were taken when the crop had received 210-320 growing degree-days (usually the mid-vegetative phase of growth). It is suggested that canola breeders may use NDVI to objectively select for vigorous genotypes that are more likely to have higher grain yields.